Editorial Vol.7(1) - Jha, Ashok Kumar (Journal of Management, 2024)
The JOM is a peer-reviewed academic research journal registered with the online academic platform NepJOL, TU Central Library, Kirtipur that offers a platform for academicians, professionals and scholars to publish their original research in the field of management, commerce studies, business Laws, economics and managerial communication. The scholarly and research articles published in the present Journal has undergone the editorial peer review process prior to publication to ensure that only the acceptable standard articles are published.